Recent Advances on the Regulations of Organic Anion Transporters - Zhou Yu; Guofeng You (MDPI AG, 2024)
The organic anion transporter (OAT) family of over 10 members within the solute carrier (SLC) superfamily of membrane proteins plays critical roles in facilitating the flux of negatively charged molecules in and out of cell membranes. These anionic molecules include various endogenous and exogenous compounds such as signaling molecules, nutrients, metabolites, toxins, and drugs. Therefore, OATs actively contribute to the systemic homeostasis and efficacy of therapeutics. This article provides a brief overview on recent advances in the understanding of the regulatory mechanisms that control the expression and activity of OATs in both health and diseases.